The Nature of Human Resource Management and Organizational Change in Malaysian Small and Medium Sized Enterprises (SMEs) - Abdullah, Nur Anisah (2000)
This study examined the broad nature of patterns and trends in the hullB.ll resource management practices and organizational change in SMEs in Malaysia, by focusing on how organizational characteristics, such as, size, union status and corporate ideology, influence the use of those practices.The data were obtained from a survey involving 219 small and medium-sized enterprises (SMEs). It is often argued that larger and older organizations have the strengths to perform better and that they have resources to implement most strategies. The discussions will clarify some geneml assumptions made on SMEs management practices. The analysis of the data revealed that most of the SMEs were in the manufacturing sector/industry. A majority of them were non-unionized. The findings of this study were divided into three sections. The first section discussed the analysis of human resource management (HRM) practices adopted by the SMEs. The second section touched on the analysis of organizational change implemented by SMEs and finally, the last section present the statistical analysis on the hypotheses testing to analyzed two models. The first model, consisted of a group of three hypotheses, is to examine the relationship between the HRM practices and the firm's characteristics. The second model, also consisted of a group of three hypotheses, is to examine the relationship between the implementation of organizational change practices and the firm's characteristics.Overall results suggest a high level of adoption of HRM practices. However, quite a number of SMEs did not hire personnellHRM specialists. Those who have hired the specialists were the larger firms. Eighty three percent of the respondents had altered their practices to achieve their goals. More changes had taken place in the past three years than in the last five years. This would indicate that there is significant degree of change being undertaken. The congruity of implementation levels of change in work practices across each firm size category has indicated that there is a need for flexible work patterns in the Malaysian SMEs. The analysis showed that SMEs of all categories implemented changes which include, for example, 'Improved in labor productivity', 'Increased competitiveness' and 'Employing new plant, equipment of technology' . It was also found that the SMEs were market-driven and competitive. The results revealed that workforce reduction was not commonly practiced. There was sufficient statistical evidence to support the first model. It was found that there is existence of some relationships between HRM and the firm's characteristics. Progressive Decision-Making Ideology (pDM), as one of the firm's characteristics, was found to be the most important determinant in the adoption of HRM practices. Firm size, as the second firm characteristic, was found to be positively related to the adoption of HRM practices but as a less important determinant.Union status, the third and last firm characteristic, was found to be negatively related, and was the least important in influencing the adoption of HRM practices in the SMEs. The second model, that is, to examine the relationship between implementation of organizational change practices and the firm's characteristics, which include, PDM, firm size and union status, was not supported statistically.